2018
DOI: 10.1111/jonm.12607
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ethical leadership and organisational commitment of nurses with perception of patient safety culture

Abstract: Implementing ethical leadership seems to be one feasible strategy to improve nurses' organisational commitment and perception of patient safety culture. Efforts by nurse managers to develop ethical leadership reinforce organisational commitment to improve patient outcomes. Nurse managers' engagement and performance in this process is vital for a successful result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 34 publications
3
68
2
1
Order By: Relevance
“…Among health professions, nurses play a key role in ensuring the quality and safety of healthcare services [1]. Recent studies have shown that high levels of organizational commitment [3,4] and job satisfaction [5] of nurses have positive effects on PSC. In addition, a PSC has positive effects on the nurses' performance [4] and hospital efficiency [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among health professions, nurses play a key role in ensuring the quality and safety of healthcare services [1]. Recent studies have shown that high levels of organizational commitment [3,4] and job satisfaction [5] of nurses have positive effects on PSC. In addition, a PSC has positive effects on the nurses' performance [4] and hospital efficiency [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that high levels of organizational commitment [3,4] and job satisfaction [5] of nurses have positive effects on PSC. In addition, a PSC has positive effects on the nurses' performance [4] and hospital efficiency [2]. Therefore, measurement of PSC provides the necessary information for promoting patient safety and helps monitoring the changes needed at any time [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Leadership is an influential element in the quality of nursing services (Lotfi, Atashzadeh-Shoorideh, Mohtashami, & Nasiri, 2018) due to the need for intra-and inter-group work (Abdelhafiz, Alloubani, & Almatari, 2016). It is a process influencing people to achieve organisational goals, which happen through different leadership styles (Leggat, Balding, & Schiftan, 2015).…”
mentioning
confidence: 99%
“…This 24-item questionnaire evaluates the level of organizational commitment at three aspects: affective aspect (items 1-8), continuance aspect (items 9-16) and normative aspect (items 17-24) using a 5-point Likert scale. The internal consistency (α) of this tool was .87 and stability equalled r = .93 (Lotfi, Atashzadeh-Shoorideh, Mohtashami, & Nasiri, 2018). In the present study, intra-class correlation coefficient (r = .9) was used to calculate the reliability of the instrument.…”
Section: Phase 1 Identificationmentioning
confidence: 87%